2017
DOI: 10.1007/s12015-017-9754-0
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Derived Retinal Pigment Epithelium: The Role of Pigmentation as Maturation Marker and Gene Expression Profile Comparison with Human Endogenous Retinal Pigment Epithelium.

Abstract: In age-related macular degeneration (AMD) the retinal pigment epithelium (RPE) deteriorates, leading to photoreceptor decay and severe vision loss. New therapeutic strategies aim at RPE replacement by transplantation of pluripotent stem cell (PSC)-derived RPE. Several protocols to generate RPE have been developed where appearance of pigmentation is commonly used as indicator of RPE differentiation and maturation. It is, however, unclear how different pigmentation stages reflect developmental stages and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…In addition to clinical cell replacement therapy applications [19], the RPE cells differentiated from human embryonic (hESC) or human-induced pluripotent stem cells (hiPSC) are valuable in retinal research as they display a mature RPE phenotype after differentiation [20][21][22][23][24]. However, there is rather limited knowledge regarding the compound permeation of small molecular-weight compounds across hESC-RPE cells [25,26], and therefore, the applicability of hESC-RPE in early drug development is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to clinical cell replacement therapy applications [19], the RPE cells differentiated from human embryonic (hESC) or human-induced pluripotent stem cells (hiPSC) are valuable in retinal research as they display a mature RPE phenotype after differentiation [20][21][22][23][24]. However, there is rather limited knowledge regarding the compound permeation of small molecular-weight compounds across hESC-RPE cells [25,26], and therefore, the applicability of hESC-RPE in early drug development is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of zinc in sub-RPE deposit formation in clinical studies are varied (see review [ 73 , 74 ]) and will require further investigations, probably with the use of methods that are able to specifically identify sub-RPE deposits in a clinical setting [ 75 , 76 , 77 ]. Changes in cell adhesion to polarity [ 78 ] and modulation of extracellular matrix organization had also been reported in AMD [ 31 , 79 ] which highlight another layer of complexity of zinc action on the RPE. As RPE activation and migration are significant clinical signs of the progression of AMD [ 80 ], this finding could point to new studies in which the clinical effects of zinc could be evaluated based on these new clinical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Also, at least one sex-specific susceptibility locus for AMD has been identified (14). Although Blenkinsop and coworkers (15) found that stem cell derived RPE essentially reflects the key features of native RPE, we recently also found that there's still considerable non-sex influenced whole genome variation between stem cell derived RPE and native RPE (16). These more or less contrasting data, may results from the fact that there are now multiple, slightly different, protocols to derive RPE from stem cells (17)(18)(19)(20).…”
Section: 2mentioning
confidence: 83%